PENATAAN PKL BEBAS BORAKS DAN FORMALIN MENUJU PRODUK UNGGULAN SEHAT DAN HIGIENIS - Rosyidah, Afifah; Purwanti, Endang; Hartanto, Djoko; Murwani, Irmina Kris; Prasetyoko, Didik; Ediati, Ratna (Universitas Djuanda Bogor, 2017)
PKL STEPULATION OF FREE STORE BORAKS AND FORMALIN TOWARDS HEALTHY AND HYGIENIC SUPERIOR PRODUCTSÂ ABSTRACTÂ The Community service is focused on getting healthy and hygienic food around the campus. In the early stages, the identification of food sold in street vendors around the campus, whether it contains borax and or formalin. If the results of identification are still found foods containing borax and or formalin, then counseling and guidance and given about alternative materials borax and or formalin, which is safe for health. 40 food samples were random taken from street vendors around the campus. The content of formalin and borax is analyzed qualitatively and quantitative using test equipmentâs. The results showed that there were 3 food samples from street vendors serving meatballs and noodles containing formalin and 5 food samples from street vendors serving food containing borax.Keywords: borax, formalin, qualitative analysis.Â ABSTRAKÂ Layanan Masyarakat difokuskan untuk mendapatkan makanan sehat dan higienis di sekitar kampus. Pada tahap awal, identifikasi makanan yang dijual oleh PKL di sekitar kampus, apakah mengandung boraks dan atau formalin. Jika hasil identifikasi masih ditemukan makanan yang mengandung boraks dan atau formalin, maka konseling dan bimbingan dan diberikan tentang bahan alternatif boraks dan atau formalin, yang aman untuk kesehatan. Sebanyak 40 sampel makanan diambil secara acak dari pedagang kaki lima di sekitar kampus. Kandungan formalin dan boraks dianalisis secara kualitatif dan kuantitatif dengan menggunakan alat uji. Hasil penelitian menunjukkan bahwa ada 3 sampel makanan dari pedagang kaki lima yang menyajikan bakso dan mie yang mengandung formalin dan 5 sampel makanan dari pedagang kaki lima yang menyajikan makanan yang mengandung boraks.